2015
DOI: 10.1136/bmjopen-2015-007591
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of a longitudinal cohort study on physical activity behaviour in physically disabled patients participating in a rehabilitation counselling programme: ReSpAct

Abstract: IntroductionStimulating physical activity behaviour in persons with a physical disability is important, especially after discharge from rehabilitation. A tailored counselling programme covering both the period of the rehabilitation treatment and the first months at home seems on the average effective. However, a considerable variation in response is observed in the sense that some patients show a relevant beneficial response while others show no or only a small response on physical activity behaviour. The Reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(84 citation statements)
references
References 89 publications
0
84
0
Order By: Relevance
“…A qualitative design using semi-structured interviews with rehabilitation professionals was chosen to gain in-depth insights about factors influencing the implementation and continuation of a physical activity promotion programme in different rehabilitation settings based on professionals' experiences, attitudes and expectations. The study is part of the Rehabilitation, Sports and Active Lifestyle (ReSpAct) study (4,5). The study protocol was approved by the ethics committee of the Centre of Human Movement Sciences of the University Medical Centre Groningen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A qualitative design using semi-structured interviews with rehabilitation professionals was chosen to gain in-depth insights about factors influencing the implementation and continuation of a physical activity promotion programme in different rehabilitation settings based on professionals' experiences, attitudes and expectations. The study is part of the Rehabilitation, Sports and Active Lifestyle (ReSpAct) study (4,5). The study protocol was approved by the ethics committee of the Centre of Human Movement Sciences of the University Medical Centre Groningen.…”
Section: Methodsmentioning
confidence: 99%
“…1 illustrates the content of the RSE programme. A detailed explanation of the RSE programme has been provided elsewhere (4,5).…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Social participation was measured using the ICF Measure of Participation and ACTivities Screener (IMPACT-S) [35]. Daily PA and sedentary behaviour were measured using the Short Questionnaire to Assess Health-enhancing physical activity (SQUASH) adapted for wheelchair use [36,37]. Previous research has found the abovementioned tests and questionnaires to be reliable and valid for specific sub-populations of the physically disabled population (Supplementary File 1) [29,30,[34][35][36][38][39][40].…”
Section: Questionnairesmentioning
confidence: 99%
“…Examples of these strategies include periodic counseling sessions focused on increasing motivation [83,84], self-management/empowerment programs combined with telephone support [85], and tailored interventions provided in a community setting [86]. …”
Section: Behavior Change Strategies Facilitate Transformationmentioning
confidence: 99%